Implementation the project-based learning using the context of Batik art in elementary mathematics learning - Samsul Pahmi; Nanang Priatna; Jarnawi Afgani Dahlan; Arif Muchyidin (Jurnal Elemen, 2022)
The integration of art into mathematics is currently still carried out by paying attention to the aesthetic value of student projects. However, its use has not been found to expand artistic or cultural values knowledge. This study aims to conduct a study related to the integration of batik art in mathematics learning on the topic of circles in elementary schools, where batik art contains not only aesthetic meaning but also cultural values and is the identity of the Indonesian nation. This research is focused on content design, the use of methods, and their effect on learning outcomes. The integration of batik art in learning is carried out to support the development of STEAM-based learning. This study used a quasi-experimental method using the design of One group posttest only with multiple substantive posttests, which was carried out in 2 different elementary schools in grade 6 with a sample of 41 students consisting of 28 female students and 13 male students. Experimental learning uses circular batik motifs as an art aspect and project-based learning (PjBL) as a learning method. Data collection was carried out using three instruments: a final student ability test, interviews, and questionnaires. The results show an increase in student learning outcomes, reducing students' anxiety levels in learning, increasing student activity, and providing alternative solutions for implementing fine arts in learning, especially mathematics, on the topic of circles at elementary school. This research is expected to provide benefits of knowledge related to how art or culture can be instilled simultaneously with lessons, especially mathematics learning for educators.